Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

solve the following quadratic by factoring: 6x^2-12x=0

Sagot :

Answer:

X=0,-2

Step-by-step explanation:

6 x ( x + 2 ) = 0 Divide each term in 6 x ( x + 2 ) = 0 by 6 . 6 x ( x + 2 ) 6 = 0 6 Cancel the common factor of 6 .  x ( x + 2 ) = 0 6 Divide 0 by 6 . x ( x + 2 ) = 0 If any individual factor on the left side of the equation is equal to 0 , the entire expression will be equal to 0 . x = 0 x + 2 = 0 Set the first factor equal to 0 . x = 0 Set the next factor equal to 0 and solve. Tap for more steps... x = − 2 The final solution is all the values that make 6 x ( x + 2 ) 6 = 0 6 true. x = 0 , − 2